2020
DOI: 10.1136/archdischild-2020-319910
|View full text |Cite
|
Sign up to set email alerts
|

Role of children in household transmission of COVID-19

Abstract: ObjectiveTransmissibility of COVID-19 by children in the household is not clear. Herein, we describe children’s role in household transmission of COVID-19.Design and settingAll paediatric COVID-19 index cases and their household members reported from 20 January to 6 April 2020 in South Korea were reviewed. The secondary attack rate (SAR) from child index case to household secondary case was calculated. Epidemiological and clinical findings of child index case-household secondary case pair was assessed.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
109
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 9 publications
11
109
0
2
Order By: Relevance
“…26,31,37,45,58,60,65,68,71,72 Estimated mean secondary attack rate for household contacts was 16.4% (95% CI, 13.4%-19.6%) and family contacts was 17.4% (95% CI, 12.7%-22.5%). One study 40 ). Secondary attack rates for household and family contacts were more than 3 times higher than for close contacts (4.8%; 95% CI, 3.4%-6.5%; P < .001) (eFigure 2 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,31,37,45,58,60,65,68,71,72 Estimated mean secondary attack rate for household contacts was 16.4% (95% CI, 13.4%-19.6%) and family contacts was 17.4% (95% CI, 12.7%-22.5%). One study 40 ). Secondary attack rates for household and family contacts were more than 3 times higher than for close contacts (4.8%; 95% CI, 3.4%-6.5%; P < .001) (eFigure 2 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Limited data suggest children have not played a substantive role in household transmission of SARS-CoV-2. 40,[103][104][105] However, a study in South Korea of 10 592 household contacts noted relatively high transmission from index cases who were aged 10 to 19 years. 51 Although children seem to be at reduced risk for symptomatic disease, it is still unclear whether they shed virus similarly to adults.…”
Section: Jama Network Open | Global Healthmentioning
confidence: 99%
“…21 In a subsequent study, the authors noted that almost all of the child index cases shared the same exposure as their adult contacts. 22 Thus, while the children developed symptoms first, it is possible that some may not have been true index cases. However, preliminary data from Italy are also concerning.…”
mentioning
confidence: 99%
“…Therefore, household contact tracing studies can be highly effective for COVID-19 prevention [2]. In South Korea, two similar studies demonstrated dissenting transmission rates within households from SARS-CoV-2 infected children [1,3]. In Europe (French Alps), a study of a cluster with twelve secondary cases included a symptomatic child who attended three schools without transmitting the virus to any of his contacts [4].…”
Section: Introductionmentioning
confidence: 99%